Analysis of neurotransmitters in Daphnia magna affected by neuroactive pharmaceuticals using liquid chromatography-high resolution mass spectrometry. (November 2019) - Gómez-Canela, Cristian; Rovira García, Xavier; Martínez-Jerónimo, Fernando; Marcé, Rosa María; Barata, Carlos
Abstract: Neurotransmission plays an essential role during the central nervous system (CNS) development. During the last years, several studies based on the changes produced in neurotransmitters of aquatic organisms caused by pharmaceuticals have been reported. Daphnia magna, the aquatic ecotoxicological model organism, shares several of the neurotransmitters targeted by antidepressant and other neuro-active drugs with vertebrates. Therefore, a method based on liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) has been applied for the first time to study the levels of 41 neurotransmitters in Daphnia magna under the effect of four different neuro-active pharmaceuticals (sertraline, venlafaxine, duloxetine and fluoxetine). In addition, the performance of LC-HRMS was studied in terms of linearity, sensitivity, intra- and inter-day precision, and overall robustness. The developed analytical method using LC-HRMS is a new tool for neurotoxicology research using the Daphnia magna model. As a result, general differences on the concentrations of those neurotransmitters exposed to the mentioned pharmaceuticals were observed. Graphical abstract: Image 1 Highlights: Neurotransmitters of Daphnia magna were fully characterized by LC-HRMS. Good recoveries and excellent sensitivity was achieved for the 44 neurotransmitters. Pharmaceuticals affected neurotransmitter system of exposed D. magna. The analytical method developed is a new powerful tool for neurobiology and neurotoxicology. Abstract : This represents the first study that evaluates the changes produced by pharmaceuticals in the neurotransmitter profiles by using liquid chromatography coupled to high resolution mass spectrometry (LC-HRMS).